Twenty years of ultrawideband: opportunities and challenges - Sipal, V; Allen, B; Edwards, D; Honary, B (2012)
It has been 20 years since the word ultrawideband (UWB) has first been used in the open literature. In these 20 years, ideas have been transformed into real products. Yet, some might object that UWB has not yet lived upto the promises of gigabit wireless. This review shows that despite some drawbacks, UWB is not only needed because of the spectrum gridlock but it can still deliver its promises, including gigabit wireless. To do so, the gap between the potential, which is achievable, and the current performance must be closed. Thus, this review identifies some main issues of UWB (range, bit error rate performance, data rate, chip complexity and issues associated by strong narrowband interference). It shows that their reasons are well understood and addressed by erudite research, which includes low complexity chip design, alternative modulation schemes, multiple antenna systems, UWB radio-over-fibre, higher band UWB and interferer detection and suppression techniques. A specific feature of this review is the cross-layer approach. The latest findings from different system layers, for example, wave propagation, are linked to the system performance or complexity. © 2012 The Institution of Engineering and Technology.